2007
DOI: 10.1038/sj.ejhg.5201958
|View full text |Cite
|
Sign up to set email alerts
|

The novel hyperekplexia allele GLRA1(S267N) affects the ethanol site of the glycine receptor

Abstract: Mutations in the GLRA1 gene, which encodes the a1-subunit of the inhibitory glycine receptor (GlyR), are the underlying causes in the majority of cases of hereditary startle disease (OMIM no. 149400). GlyRs are modulated by alcohols and volatile anesthetics, where a specific amino acid at position 267 has been implicated in receptor modulation. We describe a hyperekplexia family carrying the novel dominant missense allele GLRA1(S267N), that affects agonist responses and ethanol modulation of the mutant recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Several in vitro studies led to the identification of distinct residues involved in ethanol potentiation (Mihic et al, 1997). S267N located in the ion channel pore is one of the key residues for ethanol modulation and has also been found in patients that suffer from hyperekplexia (Becker et al, 2008). This mutant displayed differences in agonist potency as well as ethanol modulation and demonstrated that a disease-associated Glra1 mutation harbors the ability to alter drug responses.…”
Section: Knock-in Mouse Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies led to the identification of distinct residues involved in ethanol potentiation (Mihic et al, 1997). S267N located in the ion channel pore is one of the key residues for ethanol modulation and has also been found in patients that suffer from hyperekplexia (Becker et al, 2008). This mutant displayed differences in agonist potency as well as ethanol modulation and demonstrated that a disease-associated Glra1 mutation harbors the ability to alter drug responses.…”
Section: Knock-in Mouse Mutantsmentioning
confidence: 99%
“…In hyperekplexia, affected neonates exhibit exaggerated startle responses and muscle stiffness following an unexpected acoustic noise or a tactile stimulus, which may result in fatal apnea. During early childhood the muscle tone returns to normal levels, but startling persists into the adulthood (Andermann et al, 1980; Shiang et al, 1993; Becker et al, 2008). Predominantly, single point mutations in the GLRA1 gene encoding the GlyR subunit α1 (GlyRα1) underlie the pathology in humans.…”
Section: Introductionmentioning
confidence: 99%
“…at ASPET Journals on May 9, 2018 jpet.aspetjournals.org cine-and taurine-induced displacement of strychnine binding, without changes in the strychnine binding per se, all have been observed in other mutations that cause deficits in the glycinergic transmission (Saul et al, 1994;Rajendra et al, 1995;Moorhouse et al, 1999;Castaldo et al, 2004;Becker et al, 2008).…”
mentioning
confidence: 95%
“…The disorder is associated with mutations of the GLRA1 gene (Rees et al, 1994;Becker et al, 2006Becker et al, , 2008, the ␤ subunit gene GLRB , and the gene encoding the glycine transporter GlyT2 (Eulenburg et al, 2006;Rees et al, 2006). The mouse mutants oscillator (Glra1 spd-ot ) Kling et al, 1997) and spasmodic (Glra1 spd ) (Ryan et al, 1994;Saul et al, 1994) carry orthologous mutations in the Glra1 gene, whereas the spastic (Glrb spa ) mouse carries a ␤ subunit mutation (Becker et al, 1992;Kingsmore et al, 1994;Mülhardt et al, 1994).…”
Section: Introductionmentioning
confidence: 99%